A newly detected exotic ambrosia beetle in Argentina: Euwallacea interjectus (Coleoptera: Curculionidae: Scolytinae) - Landi, Lucas (2019)
An exotic species of ambrosia beetle (Coleoptera: Curculionidae: Scolytinae) of Asian origin has been detected recently in Argentina. Euwallacea interjectus (Blandford) has been collected infesting cultivated poplars in the Paraná Delta region. Identification was based on morphology and on DNA sequences of the COI gene. This finding adds to the increasing number of recent introductions of exotic ambrosia beetles into South America.